Pro SQL Server 2005 - Dewson, Robin; Machanic, Adam; Narkiewicz, Jan D.; Rizzo, Thomas; Sack, Joseph; Walters, Robert; Skinner, Julian; Davidson, Louis (Apress : Imprint: Apress, 2006)
SQL Server 2005 is a dramatically expanded and enhanced version of SQL Server 2000 that not only makes SQL Server a true enterprise-level RDBMS, but also changes how SQL Server professionals design databases and develop database applications. Pro SQL Server 2005 provides in-depth coverage of new SQL Server features and enhancements. It focuses on what experienced SQL Server database administrators, developers, and business intelligence practitioners need to know to get up to speed with SQL Server 2005 as quickly as possible. It carefully presents each new feature and precisely illustrates the feature with examples that show you how to use it effectively. The authors provide practical, in-depth coverage of the core topics that they specialize inall supported by realistic examples, so you'll be able to design and implement your own SQL Server 2005 solutions quickly and painlessly. This book is a roadmap for exploring and exploiting SQL Server 2005. So fasten your seatbelts, start your computers, and race to mastery of SQL Server 2005!